Family Institution and Gender Equality: A Comparative Study in Islam and Feminism Perspective - Muhammad Syamsul Al Biruni; Dr. Muhammad Alif Jamal (Al-Qanṭara, 2022)
Abstract Feminism is a fascinating topic of discussion right now. Problems such as family institution rights and obligations, male leadership, and inequality against women were viewed as clearly patriarchal, oppressive, and dominant in regulating women and quite discriminatory against them. Nonetheless, women's leadership was managed passively in family institutions. As a result, gender equality is based solely on social phenomena and environmental considerations, rather than religious values. In contrast, Islam views justice and leadership not only from material and empirical perspectives, but also from metaphysical and spiritual ones. According to Islam, men and women require respect and love that is harmonious and balanced. This paper will look at justice and equality from the perspectives of feminism and Islam. Using theological and philosophical perspectives.